O "domaku", "gniazdoszu", "zapiecniku"? Zapomniane synonimy leksemu domator w polszczyźnie = "Domak", "gniazdosz", "zapiecnik"? The obsolete synonyms of the lexeme domator in the Polish language - Piela, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The basic purpose of the article is to present the semantic history of the noun "domator" and its past synonyms in the history of the Polish language. It turns out that our linguistic ancestors understood this noun in a different manner that the modern Polish people.
Keywords: diachronia; synchronia; leksyka; semantyka; słowotwórstwo; synonim; diachronic linguistics; synchronic linguistics; lexis; semantics; word formation; synonyms